Prediction Model for Infertility in Women of Reproductive-Age Couples (WRA) - Zahrotul Fajrin Ramadhanti; Astuti, Rahayu; Wardani, Ratih Sari; Rejeki, Sri; Sayono (Public Health of Indonesia, 2025)
Background: Infertility has affected millions of people worldwide but remains a frequently overlooked issue. Infertility is common among reproductive-age couples. Approximately one in six people experience infertility, and failed pregnancies among married reproductive-age couples are attributed to female factors in 40% of cases. Objective: To identify the factors influencing infertility in women of reproductive-age couples (WRA). Methods: A retrospective cohort study was conducted by collecting medical record data and interviewing 192 women of reproductive age at a hospital from January to December 2023. The sampling techniques used were quota sampling and consecutive sampling. Bivariate and multivariate analyses were used in this study to assess how risk variables affected infertility. Results: Women experiencing infertility had a higher proportion associated with age at menarche (p = 0.012), menstrual cycle (p = 0.010), nutritional status (p = 0.003), tubal disorders (p = 0.038), duration of marriage (p = 0.000), history of miscarriage (p = 0.016), history of surgery (p = 0.019), and coffee consumption (p = 0.043). The logistic regression equation is:Log (p / 1 – p) = -8.104 + 1.877 (age at menarche) + 1.598 (duration of marriage) + 1.192 (nutritional status) + 1.146 (history of miscarriage) + 0.805 (tubal disorders). Conclusion:Risk factors influencing infertility in women of reproductive age include age at menarche, nutritional status, tubal disorders, duration of marriage, and history of miscarriage. The most influential risk factor for infertility in reproductive-age women is age at menarche (p = 0.001) with an RR value of 6.535.  Keywords: Infertility; prediction model; infertility factors; reproductive-age women